2004
DOI: 10.1111/j.1365-2788.2004.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia‐spectrum psychoses in people with and without intellectual disability

Abstract: People with ID and SSP appear to be more debilitated by the co-occurring disorder than those with the same disorder but without ID. Increases in observable psychopathology and "negative" schizophrenic symptoms, and decreased functional abilities were observed in the group with ID when compared to the GAMH group. The clinical implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Few studies have assessed the functional disability comparing ID and ID-MD. Consistent with our results, Bouras et al (2004) found that people with ID and schizophrenia have lower functioning than those with ID alone.…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have assessed the functional disability comparing ID and ID-MD. Consistent with our results, Bouras et al (2004) found that people with ID and schizophrenia have lower functioning than those with ID alone.…”
Section: Discussionsupporting
confidence: 82%
“…Auditory hallucinations have been shown to be the most reliable and consistentlyreported psychotic symptom in those with mild ID (Meadows et al 1991;Moss et al 1996). Bouras et al (2004) compared people diagnosed with schizophrenia spectrum disorders with and without mild ID. The study found that although the groups did not differ in terms of reported psychopathology, the group with ID showed greater levels of observable psychopathology and more negative symptoms (Bouras et al 2004).…”
Section: Difficulties In Recognising and Diagnosing Psychotic Disordementioning
confidence: 99%
“…Bouras et al (2004) compared people diagnosed with schizophrenia spectrum disorders with and without mild ID. The study found that although the groups did not differ in terms of reported psychopathology, the group with ID showed greater levels of observable psychopathology and more negative symptoms (Bouras et al 2004). This finding was corroborated by a meta-analysis of studies comparing the presentation of schizophrenia in people with mild ID or borderline intellectual functioning with those with average-high IQ which demonstrated those with lower IQ experience substantially greater negative symptoms (Welch et al 2011).…”
Section: Difficulties In Recognising and Diagnosing Psychotic Disordementioning
confidence: 99%
See 1 more Smart Citation
“…Dykens (2000) suggested that adolescents and children with intellectual disabilities have a significantly greater risk of psychiatric disorders as compared to their peers without intellectual disability. Comparatively speaking, the incidence of behavioural disorders is 5 -7 times more among people with intellectual disabilities (Dykens and Hodapp, 2001;Emerson, 2003;Bouras et al, 2004). Reiss (1994) noted that persons with intellectual disabilities are at higher risk of developing a mental illness than those with average intelligence.…”
Section: Introductionmentioning
confidence: 99%